2016
DOI: 10.1093/infdis/jiw195
|View full text |Cite
|
Sign up to set email alerts
|

Dually Active HIV/HBV Antiretrovirals as Protection Against Incident Hepatitis B Infections: Potential for Prophylaxis

Abstract: Our study suggests that DAART, independently of CD4 cell count and risky behavior, has a potentially strong public health impact, including pre-exposure prophylaxis of HBV coinfection in the HIV infected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
(55 reference statements)
3
39
0
Order By: Relevance
“…Our study is unique in that it showed a protective effect of 3TC only containing regimens in a population where heterosexual HIV transmission is believed to dominate. HIV viral load suppression on ART was a strong predictor of the protective effect of ART against incident HBV in our study, consistent with earlier findings (14, 15). The mechanism of this effect could be direct suppression of HBV replication or inhibition of HIV replication altering the biology of HBV acquisition.Failure to suppress HIV could also be associated with poor adherence and higher risk behaviors that predispose to HBV infection (16).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study is unique in that it showed a protective effect of 3TC only containing regimens in a population where heterosexual HIV transmission is believed to dominate. HIV viral load suppression on ART was a strong predictor of the protective effect of ART against incident HBV in our study, consistent with earlier findings (14, 15). The mechanism of this effect could be direct suppression of HBV replication or inhibition of HIV replication altering the biology of HBV acquisition.Failure to suppress HIV could also be associated with poor adherence and higher risk behaviors that predispose to HBV infection (16).…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies from the European Union and Japan also have suggested a pre-exposure protective effect of HBV active ART medications particularly TDF and 3TC (12-14). Our study is unique in that it showed a protective effect of 3TC only containing regimens in a population where heterosexual HIV transmission is believed to dominate.…”
Section: Discussionmentioning
confidence: 99%
“…[15] ). We tested the association of ART (exposure) and syphilis incidence (outcome variable), where ART was coded in several hierarchical ways: ART as a binary variable; ART divided into 4 classes of nucleotide reverse transcriptase inhibitors (NRTI), non-nucleotide reverse transcriptase inhibitors (NNRTI), protease inhibitors (PI), and other HIV antiretroviral drug classes (integrase and fusion inhibitors, primarily Raltegravir [87%]); ART divided into NRTI, PI, other HIV antiretroviral drug classes, and the individual drugs for the NNRTI class (as drugs of this class showed a weak protective association [table S1]).…”
Section: Discussionmentioning
confidence: 99%
“…[15] In addition, ART has been shown to have a wide array of targets and functions including activity as antitumor, antibacterial, antifungal, antimalarial, anti-Severe acute respiratory syndrome and anti-influenza agent. [16] …”
Section: Introductionmentioning
confidence: 99%
“…Our HIV positive population has much higher levels of vaccination than their HIV negative peers due to an active vaccination program. Furthermore lamivudine, tenofovir and emtracitabine, the most commonly used antiretroviral drugs, are known to have a powerful protective effect against HBV infection [26]. Cox regression analysis was not performed on cases of possible incident HBV infection.…”
Section: Discussionmentioning
confidence: 99%